PENYULUHAN MANFAAT EKOLOGIS DAN DAMPAK HUKUM BAGI PENGRUSAKAN HUTAN MANGROVE BAGI MASYARAKAT DESA PANTE DEERE, KECAMATAN KABOLA KABUPATEN ALOR - Plaimo, Paulus; Wabang, Imanuel Lamma; Laoepada, Setia Budi; Lakalet, Lestari; Tanglaa, Thomas John; Takalapeta, Iriantini M. J. (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This Community Service activity aims to change the pattern of understanding of the people who inhabit the coast of Pante Deere Village, who often exploit mangrove plants, which has the potential to result in a decrease in the population of mangrove plants which has an impact on the stability of the life of mangrove association organisms which make mangroves as niche and ecological niches and even legal repercussions for unscrupulous mangrove forest cutters. The process of community service activities is carried out through counseling, lectures, discussions, and question-and-answer sessions with target partners, namely the coastal community of Pante Deree Village, comprising a total of 64 family heads. In general, it is classified into several stages, among others, the Preparation Stage, Implementation Stage, and Evaluation Stage. This community service activity was declared successful, significantly, namely 90%, because there were changes in knowledge and understanding experienced by partners. It is reflected in the ability to understand and be able to apply it after this community service activity is completed.